Prevalence of bifid and trifid mandibular canal by panoramic radiograph at RSGM Unsyiah Banda Aceh: data from April 2012 to March 2017 - Kemala HAYATI; FAKHRURRAZI .; Tiara Anggraini PUTRI (Dentistry Faculty, 2020)
The mandibular canal bifid and trifid are variations of the mandibular canal. This variation of themandibular canal is essential to recognize in surgical procedures involving mandibles, such as extraction ofimpacted third molars, dental implant treatment, and sagittal split ramus osteotomy. The purpose of this study wasto determine the prevalence of bifid and trifid mandibular canal by panoramic radiograph at RSGM Unsyiah BandaAceh. This research method is descriptive by collecting secondary data in the form of panoramic images frompatients visiting RSGM Unsyiah Banda Aceh for April 2012-March 2017. A total of 2,478 panoramic radiographphotos collected showed the bifid mandibular canal is 1.25%. Based on sex, 21 photos (67.74%) of the bifidmandibular canal cases in women and ten photos (32.26%) in men. Based on the position of the bifid mandibularcanal, 9 images (29.03%) unilateral/ right-sided, 15 photos (48.39%) were unilateral/left side, and seven photos(22.58%) bilateral. KEYWORDS: bifid mandibular canal, panoramic, prevalence, trifid mandibular canal